KRITERIA PENILAIAN KARYA BAHAN LUNAK - Hasnawati Hasnawati; Yabu Malabasa; Pangeran Paita Yunus (TANRA: Jurnal Desain Komunikasi Visual Fakultas Seni dan Desain Universitas Negeri Makassar, 2018)
This study aims to develop a tool in the context of learning local culture in ceramics craft learning which can be used as a guidebook by cultural arts teachers in junior high schools. This type of research is a study adapted from the development research model of Borg & Gall. The flow of this research starts with the analysis of academic needs, strategy learning, instrument development, instrument development, instrument development, instrument realization, development. Data collection techniques are done by techniques, interviews, documentation, and questionnaires. The team of experts in this research are material media and media experts, to assess the validity of the instruments developed. The trial subjects were junior high school teachers in Makassar City. Data analysis was performed with qualitative and quantitative descriptive analysis techniques. Based on the results of the research that has been done, it can be concluded that the instruments developed in this study are ceramic craft learning instruments. ranking along with user guidelines. Some steps taken in developing association-based organizations in accordance with local culture, namely analysis of teacher needs (field studies and literature studies), development of learning activities (looking at curriculum, standards, developing indicators, and developing instruments)), developing instruments, analyzing, and evaluation. These instruments state that the calculation varies according to what has been applied and applies to a period of validity and practical results of practicality. The instruments developed have been located by junior high school teachers in Makassar City.